Dynamic effect of disaggregated level electricity generation on residential carbon emissions: Daily inference from the largest EU economies - Pata, Ugur Korkut; Kartal, Mustafa Tevfik; Alola, Andrew Adewale; Depren, Serpil Kilic (ELSEVIER, 2024)
This study examines the dynamic effects of electricity generation (EG) on CO2 emissions from the residential sector. The study focuses on the EU-4 countries (Germany, Spain, France, and Italy), considers residential CO2 emissions as the dependent variable, and includes disaggregated level fossil and renewable EG as explanatory variables. In this context, the study runs nonlinear quantile-on-quantile (QQ) regression and Granger causality in quantiles (GQ) as the main models with daily data from January 2, 2019, to March 10, 2023, while quantile regression (QR) is used for robustness check. The findings present that in terms of CO2 emissions: (i) EG from coal, natural gas, and oil has a stimulating effect at higher quantiles in all countries; (ii) EG from hydro has an increasing effect at higher quantiles, while it has a decreasing effect at lower and middle quantiles in all countries except France; (iii) EG from solar has a dampening effect at higher quantiles in all countries except France; (iv) EG from wind has a declining effect at higher quantiles in both Spain and France; (v) both fossil and renewable energy EG have a causal effect on residential sector CO2 emissions at the disaggregated level except at some quantiles. Overall, the effect size and the causal effect of EG on CO2 emissions change for quantiles, countries, and EG sources. Therefore, the study proposes to rely on the specific EG sources for Germany and Italy (solar energy), Spain, and France (wind energy) to mitigate climate change by reducing residential CO2 emissions.
Keywords: Residential sector; Renewable electricity; Fossil electricity; European countries; Nonlinear approaches; RENEWABLE ENERGY-CONSUMPTION; CO2 EMISSIONS; CLIMATE-CHANGE; URBANIZATION; GROWTH; FOSSIL; MARKET; CHINA; Energy & Fuels